Industrialization, urbanization and CO₂ emissions in Saudi Arabia: Asymmetry analysis - Haider Mahmood; Tarek Tawfik Alkahteeb; Maham Furqan (Energy Reports, 2020)
Keeping a sustainable environment is always a massive challenge for oil-exporting countries, and in that situation, industrialization and rapid growth of urbanization can add fuel to the fire. We investigate the effects of industrialization and urbanization on the CO2 emissions per capita in Saudi Arabia, utilizing an annual period 1968-2014. The results show that both industrialization and urbanization impede the environment with the inelastic effect of industrialization and elastic effect of urbanization on the emissions. An asymmetry in the relationship of industrialization and emissions is also found. The increasing industrialization has larger environmental effect than decreasing industrialization. We recommend the Saudi government to design tighter urban and industrial-environmental policies to put a halt on increasing CO2 emissions.
Keywords: 330; Asymmetry; CO2 emissions; Industrialization; Urbanization